THE DOCTRINE OF MODERN CONSTITUTIONAL LAW OF THE REPUBLIC OF AZERBAIJAN AS AN AXIOLOGICAL PHENOMENON IN THE PARADIGM SYSTEM OF THE WORLD CONSTITUTIONALISM - Gadimaliyev, A.R (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
As the axiological phenomenon in the paradigm of the world constitutionalism, the features of the doctrine of the modern constitutional right of the Republic of Azerbaijan. The aim of the study is to define the scientific foundations of the doctrine of the modern constitutional law of the Republic of Azerbaijan, the scientific-methodical evaluation of its constitutional bases, the study of the theories connected with the constitutional right doctrine and summarizing the results of scientific researches related to their application in practice. The amendments and additions to the Constitution of the Republic of Azerbaijan, as well as other normative legal acts containing constitutional legal norms were investigated. The article discusses the main concepts and some features of constitutional reforms in modern times. The main purpose of the research is the scientific and methodological assessment of modern constitutional reforms, the study of theories related to constitutional reforms and the generalization of the results of scientific research related to their application in practice. There is also a study of amendments and additions to other normative legal acts, including constitutional law. As a result of the research, both local and foreign experience on the subject was studied, and attitudes to the existing problems in this field were expressed. The doctrine of the modern constitutional right of the Azerbaijan Republic has been studied as an axiological phenomenon in the paradigm of the world constitutionalism. Both domestic and international experience on the subject has been studied, and attitude to the current problems has been reported. The current legal literature, a normative legal base has been analyzed; some recommendations and suggestions have been made.